Rectal glands and tergal glands as sources of volatile pheromones in cucumber fruit fly, Zeugodacus Cucumis - Soo J Park; Jeanneth Pérez; Vivian Mendez; Phillip W Taylor (Scientific Reports)
Abstract Male tephritid fruit flies typically emit pheromones from rectal glands to attract mates. Consistent with this, virgin females of the cucumber fruit fly, Zeugodacus cucumis (French), were found to be attracted to volatiles emitted by crushed male rectal glands in Y-tube olfactometer bioassays. Electrophysiological studies identified several male rectal gland compounds that triggered responses in female antennae. In other studied tephritids, the proportion of each compound is similar in excised rectal glands and headspace of calling intact flies, but our initial investigations revealed substantial discrepancies in the abundance of aliphatic amides, suggesting additional sources of these compounds. To address the discrepancies, we examined the volatile chemistry of headspace, rectal glands, tergal glands, and cuticles from both sexes using gas chromatography-mass spectrometry (GC-MS). Our analyses confirmed previously identified compounds and also detected several previously unreported compounds. Notably, the aliphatic amides were found to be more abundant in both tergal glands and cuticle than in rectal glands in both sexes, suggesting glands associated with these sites as additional sources of these compounds in headspace. Most studies of tephritid sex pheromones have focused on rectal gland extracts, but insights of the present study indicate that headspace volatiles of live flies can also reflect contributions from other glands.